2020
DOI: 10.1007/s00345-020-03171-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of ultrasonography, computed tomography, cystoscopy and cytology to detect urinary tract malignancies in patients with asymptomatic hematuria

Abstract: PURPOSE: To report the incidence of urinary tract malignancies (UTM) and to compare the diagnostic accuracy of cytology with cystoscopy, renal ultrasound (US) and computed tomography (CT) in patients with hematuria. METHODS: A retrospective analysis was conducted of patients who underwent cystoscopy, cytology, US and CT for hematuria between 2011 and 2017. Age, gender, BMI, smoking status, and results of further diagnostic interventions including transurethral resection of the bladder (TURB), ureterorenoscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…There are many possible benign urologic or systemic aetiologies for haematuria, and it is also possible that visible haematuria is a progression of non-visible haematuria in patients with UUT cancers. It is however important to highlight that no UUT mitotic lesion was diagnosed following presentation with non-visible haematuria in this study; supporting previous publications demonstrating that UUT malignancies are a rare occurrence in non-visible haematuria [3], [23].…”
Section: Discussionsupporting
confidence: 88%
“…There are many possible benign urologic or systemic aetiologies for haematuria, and it is also possible that visible haematuria is a progression of non-visible haematuria in patients with UUT cancers. It is however important to highlight that no UUT mitotic lesion was diagnosed following presentation with non-visible haematuria in this study; supporting previous publications demonstrating that UUT malignancies are a rare occurrence in non-visible haematuria [3], [23].…”
Section: Discussionsupporting
confidence: 88%
“…6 Published papers also show that MH can occur due to urothelial cancer, including bladder and upper tract malignancy. 12,13 The present study contained some methodical differences from the above-mentioned studies. First, we included in the study only the patients who had undergone a complete urological evaluation so that we would not miss any malignant lesion.…”
Section: Ta B L E 2 Multiple Logistic Regression Analysis Results and Odds Ratiosmentioning
confidence: 82%
“… 8 , 52 Further harm is associated with false-positive findings, which may produce consequences through either invasive diagnostic assessments, repeated imaging, or even partial or radical nephrectomy. 9 , 24 , 27 , 30 Halpern et al 7 reported that the additional diagnostic benefit of CT urography vs ultrasonography for evaluating MH would cost $6 480 484 per additional tumor detected. Therefore, the AUA updated its 2012 recommendation, 53 in which it endorsed upper urinary tract imaging using CT urography for all patients, to recommend restricting CT urography to high-risk patients (ie, women or men aged ≥60 years, >30 pack-years, >25 RBCs per HPF on a single urinalysis, or history of gross hematuria) in its 2020 guidelines.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 4 Ultrasonography has acceptable sensitivity for detection of KCC and a high negative predictive value for UTUC among patients with MH. 6 , 9 Furthermore, ultrasonography is cost-efficient and does not expose patients to harmful radiation. 7 , 8 A recent systematic review and meta-analyses by Jubber et al, 56 which found similar detection rates, also recommended using ultrasonography as first-line imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation